Levels of Maternal Care: Obstetric Care Consensus No, 9. Issue 2 (August 2019) - N/A,
Abstract : ABSTRACT: Maternal mortality and severe maternal morbidity, particularly among women of color, have increased in the United States. The leading medical causes of maternal mortality include cardiovascular disease, infection, and common obstetric complications such as hemorrhage, and vary by timing relative to the end of pregnancy. Although specific modifications in the clinical management of some of these conditions have been instituted, more can be done to improve the system of care for high-risk women at facility and population levels. The goal of levels of maternal care is to reduce maternal morbidity and mortality, including existing disparities, by encouraging the growth and maturation of systems for the provision of risk-appropriate care specific to maternal health needs. To standardize a complete and integrated system of perinatal regionalization and risk-appropriate maternal care, this classification system establishes levels of maternal care that pertain to basic care (level I), specialty care (level II), subspecialty care (level III), and regional perinatal health care centers (level IV). The determination of the appropriate level of care to be provided by a given facility should be guided by regional and state health care entities, national accreditation and professional organization guidelines, identified regional perinatal health care service needs, and regional resources. State and regional authorities should work together with the multiple institutions within a region, and with the input from their obstetric care providers, to determine the appropriate coordinated system of care and to implement policies that promote and support a regionalized system of care. These relationships enhance the ability of women to give birth safely in their communities while providing support for circumstances when higher level resources are needed. This document is a revision of the original 2015 Levels of Maternal Care Obstetric Care Consensus, which has been revised primarily to clarify terminology and to include more recent data based on published literature and feedback from levels of maternal care implementation.